Teaching English and poetry: a post-method and intercultural proposal - Campos, Valeria Hernandorena Monteagudo de; Bullio, Paula Cristina; Silva, Julia Roll (The ESPecialist, 2025)
This paper seeks to analyze possibilities of using teaching practices, outside the traditional scope, but guided by the Post-Method, in order to work with literary texts in English with the purpose of bringing into the final years of elementary education aspects beyond grammar and with a focus on intercultural issues. Regarding methodology, a bibliographic research is carried out on the Post-Method (Kumaravadivelu, 1994), on the conceptions of language, decoloniality and critical education (Freire, 1997; hooks, 2013; and Canagarajah, 2023), interculturality (Weissmann, 2018), as well as the Brazilian National Curriculum Base (Brazil, 2018), which, by defining English as ‘Lingua Franca’, recognizes it as a language that enables contact with other cultures. Examples of possible activities are presented, which privilege diversity and are accompanied by the BNCC skills and the macro and micro strategies specific to the post-method, which aim to propose practices that exercise the critical and sensitive eye, in addition to expanding the cultural, artistic, linguistic and political repertoire of students. In this sense, this paper provides a way to think about poetry in English and its literacy in the classroom, providing an opportunity to understand the diversity of this textual genre, as well as its importance and social relevance, through the implementation of a post-method pedagogy, offering an opportunity to transform the role of the teacher and the student in the classroom and granting them autonomy.